Enhancing students’ speaking skill through a game-based learning innovation of family game show - Ria Arista Asih; Hermiyanti Tri Halisiana (JINoP (Jurnal Inovasi Pembelajaran), 2022)
Gamification and game-based learning (GBL) is the newly introduced learning strategies considered fit for English fun learning. . This study aims to investigate the implementation of teaching Speaking in Foreign Language for Specific Purposes (FLSP) at Universitas Muhammadiyah Malang. The employed research design was Classroom Action Research (CAR) with two cycles. The GBL employed was modified from the Family 100 and Trivia game show. Subjects of the study were the Psychology students 2021/2022. Data collection methods were a survey and observation checklist, and the obtained data were analyzed using Activity Theory. The data triangulation was obtained by comparing researchers’ observation notes and questionnaire responses. . Results show that students were not enthusiastic when learning about Speaking through games.  Their enthusiasm increased when the game level, rules, and topics were adjusted. The findings of this study imply that GBL enhanced students’ understanding, motivated their learning, and increased their positive behaviours